Efektivitas Persatuan Advokat Wanita Indonesia (Pawin) Dalam Pemberian Bantuan Hukum Terhadap Pelaku Tindak Pidana Perempuan - Ayu Prasetya Dewi; I Nyoman Gede Sugiartha; Ni Made Puspasutari Ujianti (Fakultas Hukum Universitas Warmadewa, 2025)
The Indonesian Women's Advocates Affiliation (PAWIN) is an organization that exists to secure and secure the nobility of ladies by giving legitimate help to female offenders who cannot bear administrations (prodeo probono). The issue is,1) how compelling is the Indonesian Women's Advocates Affiliation (PAWIN) in giving lawful help to female hoodlums? And 2) what are the deterrents and endeavors of the Indonesian Women's Advocates Affiliation (PAWIN) in giving legitimate help to ladies who commit violations?The method used is empirical legal research. The purpose of this study is to analyze the effectiveness of the Indonesian Women's Protection Association (PAWIN) and analyze the obstacles and efforts faced by the Indonesian Women's Protection Association (PAWIN). The method used is the empirical law of experimentation with a sociological approach. The data sources used are primary data from news sources and secondary data from legal documents. The results of this study explain the effectiveness of the Indonesian Lawyers Association (PAWIN) in providing legal support as well as the obstacles and efforts of the Indonesian Women Lawyers Association (PAWIN) in providing legal support.